2021 IEEE Global Communications Conference (GLOBECOM) 2021
DOI: 10.1109/globecom46510.2021.9685348
|View full text |Cite
|
Sign up to set email alerts
|

ECHO: Enhanced Conditional Handover boosted by Trajectory Prediction

Abstract: Conditional handover (CHO) has been introduced in 5G to improve mobility robustness, namely, to reduce the number of handover failures by preparing target Base Stations (BSs) in advance and allowing the user to decide when to make a handover. This algorithm constantly prepares and releases BSs, thereby adapting to the fast changing radio condition. A user might make a handover to a distant BS that has a favorable channel only for a short time due to signal fluctuations. This increases the handover rate and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A. Prado et al introduced enhanced CHO (ECHO) based on the user's mobility and reserved resources in that trajectory. Then, they developed a sequence to sequence (Seq2Seq) prediction model which reduces handover rate up to 23% , RLFs up to 77% and control messages up to 69% [46]. The simulations of baseline handover proved that CHO decreases the RLF and the system recovery process accelerates reconnections up to 80% despite RLF occurrence [47].…”
Section: Conditional Handovermentioning
confidence: 99%
“…A. Prado et al introduced enhanced CHO (ECHO) based on the user's mobility and reserved resources in that trajectory. Then, they developed a sequence to sequence (Seq2Seq) prediction model which reduces handover rate up to 23% , RLFs up to 77% and control messages up to 69% [46]. The simulations of baseline handover proved that CHO decreases the RLF and the system recovery process accelerates reconnections up to 80% despite RLF occurrence [47].…”
Section: Conditional Handovermentioning
confidence: 99%
“…For the efficient distribution of resources in the network, it is important that resource reservation time is optimized. It is known from [12], [14], [19] that the resource reservation time in CHO is high since multiple cells reserve resources for a single UE. In [6] it was concluded that in FCHO the resource reservation problem is exacerbated due to the retention of prepared cells after a handover.…”
Section: Introductionmentioning
confidence: 99%